The Standard Model of Particle Physics and What Lies Beyond: A View from the Bridge - Pran Nath (Condensed Matter, 2025)
The standard models of particle physics and of cosmology have been enormously successful in correlating a large amount of data. However, there are missing pieces and we are still far from what the ultimate model may look like. We give a broad perspective of both the achievements and of the missing pieces and discuss what may lie beyond.